Viajando con Don Quijote en el siglo XXI - Odilíe Rojas-López (Revista Electrónica Educare)
Don Quixote has ridden with us for a long time now, and as if his fight against windmills were not enough, Don Quixote still has many more difficult situations to combat in the present times. Will the Knight of the Sad Figure accomplish this new deed?